A Literature Review On The Structure-Activity Relationship (SAR) Approach In The Optimization And Development Of Anticancer Compounds As Drug Candidates - Saeful Amin; Annisa Nurwafi; Jingga Ramdhina; Putri Nuraisyah (International Journal of Health Engineering and Technology, 2026)
Cancer is one of the leading causes of death worldwide, with increasing incidence and mortality rates, highlighting the urgent need for more effective and selective therapeutic strategies. One widely used approach in medicinal chemistry is the Structure–Activity Relationship (SAR), which aims to understand the relationship between the chemical structure of compounds and their biological activity. This study aims to analyze the role of the SAR approach in the optimization and development of anticancer compounds as drug candidates through a literature review of 15 scientific journals. The method used is a descriptive-comparative approach by evaluating parameters such as compound structure, types of substituents, biological activity, and mechanisms of action. The results indicate that structural modifications, including the addition of hydroxyl, methoxy, and halogen groups, as well as molecular hybridization strategies, significantly enhance anticancer activity, as reflected by IC₅₀ values ​​in the micromolar to nanomolar range. Furthermore, modified compounds tend to exhibit higher selectivity and more specific mechanisms of action toward biological targets. Therefore, the SAR approach is proven to be effective as a foundation for the rational design of more optimal anticancer compounds. The implications of this study suggest that integrating SAR with biological evaluation and formulation development may lead to more effective and safer anticancer drug candidates.